2008
DOI: 10.1159/000118661
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Hydrolyzing Oxacillinase, OXA-48, Persists in <i>Klebsiella pneumoniae</i> in Istanbul, Turkey

Abstract: Background: Two OXA-48-producing Klebsiella pneumoniae isolates(KP-4936 and KP-154488) were analyzed. Method: Minimum inhibitory concentrations were determined using agar dilution and E-test, β-lactamase production by phenotypic tests (E-test MBL and ESBL, isoelectric focusing, and bioassay) and molecular methods (PCR, RAPD-PCR, sequencing, plasmid analysis, and conjugation). Results: Isolateswere resistant to all β-lactams, including carbapenems. PCR and sequencing identifiedblaOXA-48in bothisolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 49 publications
0
14
0
5
Order By: Relevance
“…This enzyme was firstly reported from a K. pneumoniae isolate in Turkey in 2001 (22). Later, it was reported from different hospitals with increased rates (29,32). A multi-central surveillance study performed at a Turkish university hospital from 2009 to 2013 showed that more than 96% of K. pneumoniae isolates harbored blaOXA-48 carbapenamese (21).…”
Section: Discussionmentioning
confidence: 94%
“…This enzyme was firstly reported from a K. pneumoniae isolate in Turkey in 2001 (22). Later, it was reported from different hospitals with increased rates (29,32). A multi-central surveillance study performed at a Turkish university hospital from 2009 to 2013 showed that more than 96% of K. pneumoniae isolates harbored blaOXA-48 carbapenamese (21).…”
Section: Discussionmentioning
confidence: 94%
“…Ambler sınıflandırmasına göre en sık gözlemlenen karbapenemazlar olan sınıf A (KPC), sınıf B (NDM, IMP, VIM) ve sınıf D (OXA-48) beta-laktamazları kodlayan genler spesifik primerler ve amplifikasyon koşulları kullanılarak PCR ile tespit edilmiştir (Tablo 1) (1,9,22,23) . Her bir reaksiyon için 10X PCR tamponu, 2 mM dNTP, 3 pmol primer, 2.…”
Section: Gereç Ve Yöntemunclassified
“…(5,6,14,15,25) . Çalışmamızda pozitif kontrol köken olarak; K.pneumoniae ATCC BAA-1705(KPC-2 pozitif köken), K.pneumoniae IMP-1 pozitif köken, P.aeruginosa VIM-4 pozitif köken, K.pneumoniae 05-506 (NDM-1 pozitif köken), K.pneumoniae 4936 (OXA-48 pozitif köken), negatif kontrol köken olarak da E.coli ATCC 25922 ve K. pneumoniae ATCC BAA-1706 kullanılmıştır (1,2,26) .…”
Section: Gereç Ve Yöntemunclassified
“…türlerinde sık görülmesine rağmen Enterobacteriaceae üyelerinde daha nadir bulunmaktadır. Ancak, ülkemizde özellikle OXA-48 aracılığıyla gelişen karbapenem direnci başta K. pneumoniae olmak üzere Enterobacteriaceae üyelerinde son yıllarda artan sıklıkta görülmüştür (48)(49)(50).…”
Section: Tedaviunclassified